Aplikasi Pembelajaran Pengenalan Nama Dan Fungsi Anggota Tubuh Bagi Anak Usia Dini - Ade Indah Permataasri; Temi Ardiansah (Journal of Data Science and Information Systems, 2023)
This research was conducted on the basis of learning needs by using information technology through macromedia flash-based electronic media to help foster interest in learning independently to be able to develop student creativity and understanding in learning. This should be introduced from the preschool level so that the potential of children can be explored from an early age. Until now the media that is often used for learning in Early Childhood Education (PAUD) is a guidebook accompanied by pictures, apart from books one can also study it with makeshift teaching aids in schools. Apart from that, other technologies that are currently developing rapidly can also be utilized, namely computers which can be used in the world of education using learning methods with learning application technology. Learning applications are expected to create better and more interactive learning in the learning process. Learning applications are generally presented with a programming language that is visualization and by using sound, text, images. In its development, learning application technology is needed in learning techniques. With the application-based learning method, it is hoped that it will increase the enthusiasm of students and the general public for the fields discussed, besides that understanding of a material will be easier to understand and understand if delivered using the visualization method.